Follicular Penetration of Caffeine from Topically Applied Nanoemulsion Formulations Containing Penetration Enhancers: In vitro Human Skin Studies - Abd, E.; Benson, Heather; Roberts, M.; Grice, J. (S. Karger AG, 2018)
Background/Aims: This study aimed to investigate transfollicular delivery enhancement of caffeine from nanoemulsion formulations incorporating oleic acid (OA) and eucalyptol (EU) as chemical penetration enhancers. Methods: Caffeine permeation was evaluated from nanoemulsions containing OA or EU and an aqueous control solution through excised human full-thickness skin with hair follicles opened, blocked, or left untreated. Differential tape stripping was performed, followed by cyanoacrylate skin surface biopsies to determine the amount of caffeine in the hair follicles, and skin extraction to determine the retention of caffeine in the skin. Results: Nanoemulsions significantly increased caffeine permeation through open and untreated skin over control (untreated: 36- and 42-fold for OA and EU, respectively; open: 40- and 49-fold). The follicular route contributed 53.7% of caffeine permeation for the OA nanoemulsion and 51% for EU when follicles were opened. Nanoemulsions promoted 4- and 3.4-fold increases in caffeine retention in open follicles, for OA and EU, respectively. Retention of caffeine in the stratum corneum and skin was almost equal in all cases. Conclusions: This study demonstrated effective delivery of caffeine as a hydrophilic model drug into and through hair follicles and showed that follicles and surrounding regions may be targeted by optimised formulations for specific treatments.